2009
DOI: 10.1007/s00449-009-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the oxidation of glutathione in protein refolding buffer

Abstract: Here, we examined the change of glutathione (GSH) under different conditions and determined the appropriate kinetic schemes to describe its change of concentration. GSH was continuously oxidized into glutathione disulfide (GSSG) as incubation period increased at the temperatures ranging from 10 to 50 degrees Celsius while certain oxidation by-products were also observed at the later stage of reaction at higher temperatures (70-90 degrees Celsius). The addition of 0.3 mM GSSG in 3 mM GSH solution delayed the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…28 The oxidation of cysteinyl in GSH was positively correlated with reaction time and reaction temperature. 24 At a molar ratio of 2:1, the yield of GSSG at 90 °C was higher than that at 80 °C during the 70 min reaction time (Figure 3b). GSSG as a diamine compound could react with Rib to produce the ARP of Rib-GSSG.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…28 The oxidation of cysteinyl in GSH was positively correlated with reaction time and reaction temperature. 24 At a molar ratio of 2:1, the yield of GSSG at 90 °C was higher than that at 80 °C during the 70 min reaction time (Figure 3b). GSSG as a diamine compound could react with Rib to produce the ARP of Rib-GSSG.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Due to the reactive sulfhydryl group, GSH was prone to undergo oxidation to produce the intermolecular coupling product GSSG during the preparation of RG-ARP (Figure a). ,, As shown in Figure d, the oxidation of GSH intensified with the increase in the reaction time, and the GSSG yield reached 8.46% after 30 min during the heat treatment, which was 1.65 times higher than the maximum yield of RG-ARP (5.12%) at the same reaction time. Thermal degradation was an important but not dominant consumption pathway of GSH during the thermal reaction (Figure a) .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…There is only the dissolved oxygen in the sample solution. It was reported that the air‐exposed sample solution can contain oxygen ~ 3.2 × 10 –4 mol/L at room temperature and 1 atm ambient pressure . The reaction products of insulin and GSH were less in sealed solution than those in air (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%